1994
DOI: 10.2172/10116371
|View full text |Cite
|
Sign up to set email alerts
|

Test documentation for the GENII Software Version 1.485

Abstract: I DEc 12 -ENGINEERING DATA TRANSMITTAL 35%\hbc\ . a \ 2. To: (Receiving Organization) Risk Methodology and P D & ' i h 12-6-59 Signature of EDT Date Originator BD-7400-172-2 (04/94) GEF097 BD- 7400-172-1 (02/89) ..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…The Bayesian clustering approach implemented in the STRUCTURE (ver. 2.3.1) software (Pritchard, 2007) was utilized to assess the population's genetic structure. K values were tested from one to ten with ten independent runs for each K and 500,000 steps followed by 106 iterations for the length of the burn-in.…”
Section: Discussionmentioning
confidence: 99%
“…The Bayesian clustering approach implemented in the STRUCTURE (ver. 2.3.1) software (Pritchard, 2007) was utilized to assess the population's genetic structure. K values were tested from one to ten with ten independent runs for each K and 500,000 steps followed by 106 iterations for the length of the burn-in.…”
Section: Discussionmentioning
confidence: 99%
“…Wright's pairwise F ST was calculated between each site using FSTAT 2.9.3.2 (Goudet 1995). The programs Structure 2.3.4 and Tess 2.3 were utilised to compare any population structure detected across the dataset, and spatial coordinate information for each sample was included in Tess to assist in assigning genetic clusters (Pritchard et al 2003;Chen et al 2007). An admixture model with correlated allele frequencies was assumed in Structure, with an initial burn-in of 300,000 and 700,000 Monte Carlo Markov Chain (MCMC) repetitions, and 15 iterations per K, ranging from K = 1-15 to reflect the number of sites sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Percentages of correct population assignment ranged from 52.6% (DUN) to 100.0% (DET, PÉL) and did not depend on population sample size (r = -0.456, p = 0.152, n = 7). Following the standard procedure (Pritchard 2000(Pritchard , 2004 to infer the most likely number of populations inherent in our data set, we concluded that K = 5 populations. However, the ΔK values for each K between 2 and 7 (K = 2: 1.21; K = 3: 15.24; K = 4: 25.84; K = 5: 13.49; K = 6: 1.83; K = 7: 2.13) suggested that K = 4 was the most likely number of populations (see…”
Section: Genetic Variation and Hardy-weinberg Equilibriummentioning
confidence: 97%